2014
DOI: 10.1021/jf500333y
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Cocoa Procyanidins Possess Enhanced Bioactivity Compared to Monomeric and Polymeric Cocoa Procyanidins for Preventing the Development of Obesity, Insulin Resistance, and Impaired Glucose Tolerance during High-Fat Feeding

Abstract: Cocoa is a major source of these flavanols. However, research on the potential anti-obesity and anti-diabetic health benefits of cocoa flavanols is lacking in the literature. Furthermore, the effect that the size of these flavanols has on the extent of its beneficial properties is also unclear. The objective of this study was to evaluate the dietary effects of cocoa flavanols on the onset of obesity, insulin resistance and impaired glucose tolerance and to determine the impact that the size of these compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 100 publications
14
102
0
Order By: Relevance
“…Consistently, the improved glucose tolerance induced by cocoa-rich diet in ZDF rats was accompanied by reduced insulin levels at short term and at long term, which points to the improved hormone sensitivity, as evidenced by a decreased HOMA-IR index. Diminished insulin values have also been reported in insulin-resistant rodents fed with procyanidins from cocoa or grapes [16,31]. Moreover, in our experimental conditions, cocoa reduced body weight of ZDF rats without affecting the food intake, which could contribute to the improved insulin sensitivity, as previously shown for high-fat fed mice supplemented with oligomeric cocoa procyanidins [16].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistently, the improved glucose tolerance induced by cocoa-rich diet in ZDF rats was accompanied by reduced insulin levels at short term and at long term, which points to the improved hormone sensitivity, as evidenced by a decreased HOMA-IR index. Diminished insulin values have also been reported in insulin-resistant rodents fed with procyanidins from cocoa or grapes [16,31]. Moreover, in our experimental conditions, cocoa reduced body weight of ZDF rats without affecting the food intake, which could contribute to the improved insulin sensitivity, as previously shown for high-fat fed mice supplemented with oligomeric cocoa procyanidins [16].…”
Section: Discussionsupporting
confidence: 85%
“…1) and fasting glucose at the end of the experiment (Table 3), respectively. In line with this, epicatechin, oligomeric cocoa procyanidins and different cocoa extracts have proved to reduce the glucose levels on diabetic rodents [16][17][18]20]. This short-term effect has been related to the suppression of glucose intestinal absorption by catechins present in cocoa in rodents [16,17], which could contribute to the post-prandial glycemic control and body weight gain, but it has also been associated to an increased postprandial insulin secretion, as shown in humans fed with cocoasupplemented diets [22].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, CPs decreased the mRNA levels of genes involved in fat uptake, including LPL, and Lipc (hepatic lipase). In the previous studies, decreased expressions of fatty acid synthase (Wang et al, 2014), hepatic lipase (Yang et al, 2013), Scd1 (Ali, Ismail, & Kersten, 2014;Ali, Ismail, & Esa, 2015;Dorenkott et al, 2014) and LPL (Bonen, Dohm, & van Loon, 2006;Gu, Yu, Park, Harvatine, & Lambert, 2014;Janowski, 2002) have contributed to impaired development of obesity and liver steatosis.…”
Section: Discussionmentioning
confidence: 95%
“…For example, an animal study found that mice that were fed a high-fat diet supplemented with an equivalent reasonable human dose of cocoa had a lower increase in fat mass compared to the high-fat control group [17]. In another study examining the anti-obesity effects of cocoa in rats found that cocoa decreased body weight gain and the weight of white adipose tissue [18].…”
Section: Chocolate Consumption and Health Statusmentioning
confidence: 99%